Harmonics, power systems, and smart grids - De La Rosa, Francisco C. (CRC Press, 2015)
Harmonics, Power Systems, and Smart Grids, Second Edition compiles the most relevant aspects of harmonics in a way that the unfamiliar reader can better grasp the subject matter and the experienced reader can directly access specific subjects of interest. The text begins with a definition of harmonics, along with analytical expressions for electrical parameters under nonsinusoidal situations, and then Discusses important and widely used industry standards to control harmonic distortion levels Describes methods to mitigate the effects of harmonics, detailing the operation principles and design of passive filters and active filter fundamentals Presents alternative methods, such as stiffer AC sources, power converters with increased number of pulses, series reactors, and load reconfiguration Reviews the elements that play a role in the study of the propagation of harmonic currents in a distribution network Explains how to determine power losses in electrical equipment attributed to harmonic waveform distortion Covers harmonics from solar and wind power converters and power electronics in FACTS and HVDC technologies Explores harmonics from electric vehicles connected to the grid, superconductive fault current limiters, and electric vehicle charging stations Featuring three new chapters, a number of new examples and figures, and updates throughout, Harmonics, Power Systems, and Smart Grids, Second Edition provides a comprehensive reference on harmonic current generation, propagation, and control in electrical power networks, including the broadly cited smart grid --Book jacket.